2016
DOI: 10.4209/aaqr.2015.11.0643
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic VOCs at Major Road Junctions of a Metropolis in India: Measurements Using TD-GC-FID and PTR-TOF-MS Instruments

Abstract: Ambient mass concentrations of benzene and toluene were measured at 12 different road junctions of Ahmedabad city in India during the pre-monsoon season of year 2015. A Thermal Desorption-Gas Chromatography-Flame Ionization Detector (TD-GC-FID) technique was used for the analysis of aromatic volatile organic compounds (VOCs) in air samples. In each of both inner and outer ring roads, air samples were collected at 6 sites to investigate the spatial variation of benzene and toluene. The mass concentrations of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Poor air quality is a serious problem in many cities of the world due to the large emissions of both gaseous and particulate pollutants from a variety of anthropogenic activities ( Carmichael et al., 2009 ; Baudic et al., 2016 ; Wang et al., 2017 ; Dias and Tchepel, 2018 ; Shah et al., 2019 ). The fast urbanization, industrial-economic growth, transportation rate, and use of fossil fuels have resulted in the increasing concentrations of key air pollutants in the South Asia region ( Sahu et al., 2016a , 2016b , 2020a ; Srivastava, 2005 ; Yadav et al., 2019 , 2017 ). Volatile organic compounds (VOCs) are important components of urban air pollution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor air quality is a serious problem in many cities of the world due to the large emissions of both gaseous and particulate pollutants from a variety of anthropogenic activities ( Carmichael et al., 2009 ; Baudic et al., 2016 ; Wang et al., 2017 ; Dias and Tchepel, 2018 ; Shah et al., 2019 ). The fast urbanization, industrial-economic growth, transportation rate, and use of fossil fuels have resulted in the increasing concentrations of key air pollutants in the South Asia region ( Sahu et al., 2016a , 2016b , 2020a ; Srivastava, 2005 ; Yadav et al., 2019 , 2017 ). Volatile organic compounds (VOCs) are important components of urban air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In major cities, aromatic VOCs are released mainly from the combustion of fossil fuels in gasoline and diesel engines, gasoline evaporation, solvent usage and bio-decomposition of wastes in landfill areas ( Chan et al., 2002 ; Filella and Penuelas, 2006 ; Ortiz et al., 2002 ; Sahu et al., 2016a ). Typically, congested traffic and stagnant wind conditions are the major factors favoring accumulations of pollutants, resulting in their concentrations ( Ho et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 As the atmospheric pollution incidents caused by VOCs become increasingly serious and prominent, it's necessary to establish a real-time continuous VOCs monitoring system to con¯rm the information of speci¯c VOCs and control the emission of them. Classical VOC analytical methods include chemical methods, liquid chromatography (LC), 14 gas chromatography-mass spectrometry (GC-MS), 15 gas chromatography-°ame ionization detector (GC-FID), 16 photo-ionization detection (PID) 17 and so on. With the continuous progress of sensors and computer technology, various online real-time VOCs detection technologies and corresponding portable instruments have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to VOCs has been associated with acute and chronic health problems, such as asthma and sick building syndrome symptoms (Madureira et al, 2015;Mendes et al, 2015;Tham, 2016;Huang et al, 2016;Sahu et al, 2016). Bocskay, et al (2010) reported that prenatal exposures to carcinogenic polycyclic aromatic hydrocarbons (PAHs) were positively associated with stable chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 99%